Dynamic Social Security after the crisis: Towards a new welfare state?. (July 2014) - Diamond, Patrick; Lodge, Guy; Matijascic, Milko
Abstract The conservative bias in social attitudes to the welfare state is manifested in entrenched support among the public for traditional welfare and social security benefits, chiefly higher pension payments and public expenditure on health care. This pattern has been reinforced by the 2008 financial crisis and the Great Recession as public support for social protection strategies geared towards "new" social risks – structural changes in labour markets, adverse demography, gender inequality, and family instability – has remained relatively weak. This pattern of resistance to change may hardly be surprising given that reforms are more often viewed by the public as a form of retrenchment with clear losers and few obvious beneficiaries. This underlines that political courage is rarely enough to achieve structural reforms of the welfare state. There will need to be clearly defined short‐term and long‐term objectives underpinned by a coherent rationale capable of persuading publics and citizens of the case for change if a more "Dynamic" system of social security is to be enacted in the industrialized countries over the next 20 years.